Online journalism - Hooffacker, Gabriele. author. aut Link
XII, 191 p. 17 illus.
Keywords: The handbook provides tips and practical guidance on copywriting for the Internet and intranet, moving images and podcasts, social networks and communities, forms and formats of the medium, and content management processes. How does one become an online journalist? Where do online journalists work? What do they need to know: journalistic craft, Internet skills, online law? How do you write teasers? How do you integrate user activities? What role do audio and video play in the cross-media web offering? How do you ensure that your content is found (search engine optimization)? This book is a translation of an original German 5th edition Online-Journalismus by Gabriele Hooffacker, published by Springer VS, imprint of Springer Fachmedien Wiesbaden GmbH, part of Springer Nature in 2020. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation. Springer Nature works continuously to further the development of tools for the production of books and on the related technologies to support the authors. The content The profession: activities and fields of work.- The medium.- Online users.- Hypertext and storyboard.- Presentation forms and multi-modal formats.- Participative forms and formats.- The law.- Training and further education.- Technical terms. The target groups Journalists Graduates and lecturers in academies and journalism schools Young professionals Lecturers and students at universities The author Gabriele Hooffacker founded the Journalism Academy in Munich and is professor for the teaching area "media-adequate content preparation" at the University of applied sciences Leipzig.